2013
DOI: 10.1186/1756-0500-6-261
|View full text |Cite
|
Sign up to set email alerts
|

Consumer perceptions of the sale of tobacco products in pharmacies and grocery stores among U.S. adults

Abstract: BackgroundPharmacy-based tobacco sales are a rapidly increasing segment of the U.S. retail tobacco market. Growing evidence links easy access to tobacco retail outlets such as pharmacies to increased tobacco use. This mixed-mode survey was the first to employ a nationally representative sample of consumers (n = 3057) to explore their opinions on sale of tobacco products in pharmacies and grocery stores.ResultsThe majority reported that sale of tobacco products should be either ‘allowed if products hidden from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…These showed that slightly more than half of San Franciscans (56%) and New Yorkers (57%) sampled favored banning tobacco sales in pharmacies [12], [14], and half of New Yorkers favored banning sales in grocery stores [12]. Support for both policies is lower nationally [15].…”
Section: Introductionmentioning
confidence: 99%
“…These showed that slightly more than half of San Franciscans (56%) and New Yorkers (57%) sampled favored banning tobacco sales in pharmacies [12], [14], and half of New Yorkers favored banning sales in grocery stores [12]. Support for both policies is lower nationally [15].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are generally consistent with previous surveys, which indicate cigarette smokers are less likely to have favorable attitudes toward tobacco-related sales restrictions in pharmacies. 6,7 However, this study is the first to document that current users of non-cigarette tobacco products are also less likely to demonstrate favorability for such policies than never users. Non-cigarette tobacco product users are an important subgroup to consider, as tobacco-free pharmacy policies typically address the diversity of tobacco products available on the market.…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies have documented general public favorability toward tobacco-related sales restrictions in pharmacy stores at national and local levels, and variations in favorability by sociodemographic characteristics and cigarette smoking status. 6,7 However, increasingly more communities across the U.S. have since implemented policies that prohibit the sale of tobacco products in these settings. 8 Moreover, the tobacco product landscape continues to diversify, and no study has assessed variations in public attitudes toward such policies by other forms of tobacco product use beyond cigarettes.…”
Section: Introductionmentioning
confidence: 99%
“…As people's living standards continue to increase, consumer demand for quality fruits and their processed products has been grown continuously (Abdul-Muhmin, 2010). Focusing on the interests of farmers, an industrial chain can combine industrial groups closely related to the production of agricultural primary products together, so as to form various relationships of market transactions, transaction integration, and contractual between different parties (Patwardhan, Mcmillen, & Winickoff, 2013). Figure 2 shows the overview of the fresh fruit industry chain generally consisting of three links: fruit planting, processing and circulation of fresh fruit, and fresh fruit consumption.…”
Section: Fresh Fruit Industry Chain and Collaboration Modelmentioning
confidence: 99%